2016
DOI: 10.1007/s10995-016-2046-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers for Successful Implementation of Interconception Care in Preventive Child Health Care Services in the Netherlands

Abstract: Objectives Successful implementation of preconception and interconception care contributes to optimizing pregnancy outcomes. While interconception care to new mothers could potentially be provided by Preventive Child Health Care services, this care is currently not routinely available in the Netherlands. The purpose of this study was to identify facilitators and barriers for implementation of interconception care in Preventive Child Health Care services. Methods We organized four focus groups in which Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…time) and too little prioritization by their organizations. This is in line with the expected barriers based on the previously published study on determinants for implementation of ICC in PCHC [28]. Together, above-mentioned studies call for a national guideline on ICC in PCHC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…time) and too little prioritization by their organizations. This is in line with the expected barriers based on the previously published study on determinants for implementation of ICC in PCHC [28]. Together, above-mentioned studies call for a national guideline on ICC in PCHC.…”
Section: Discussionsupporting
confidence: 86%
“…This study was based on four focus group discussions with in total 33 stakeholders representing different backgrounds (i.e. PCHC physicians, PCHC nurses, pediatricians, gynecologists, midwives, GPs, and policymakers)[28]. Barriers that emerged from this study included the lack of consensus about how ICC should be organized, possible financial and logistical barriers in PCHC services that are normally organized around child care instead of maternal care, and municipal differences in PCHC services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Implement routine preconception care in the immediate postpartum period following every delivery or pregnancy loss (interconception) [282]. This approach would have the following advantages/aims:…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Another study identified educational campaigns, local adaption, and general agreement or guidelines for standard procedures as important tools for successful implementation [4]. To identify and describe barriers to implementation in healthcare, a structured decision-support procedure has been specified as crucial [5].…”
Section: Introductionmentioning
confidence: 99%